A Trans-Scale Study on the Influence of Water Content and Particle Size on Matric Suction - Cheng Pu; Fengyin Liu; Yuetao Li; Zhaolin Zeng (Geofluids, 2023)
Exploring the water retention properties of unsaturated soil from the perspective of a liquid bridge has been a popular issue in recent years. This study first measures the soil–water characteristic curves (SWCCs) of granular specimens to determine the influence of particle size on matric suction from a macroscopic perspective. Then, the internal mechanism of the influence of particle size and volumetric water content on matric suction is analyzed from the mesoscopic perspective by using the Young–Laplace (Y–L) equation to calculate matric suction between two equal spheres. The macroscopic and mesoscopic experiments both show that matric suction decreases with an increase in particle radius. Moreover, identifying the internal mechanism of SWCC from the liquid bridge perspective is only applicable when the influence of gravity can be disregarded or is in the transitional stage. The influence of volumetric water content and sphere radius on matric suction is mostly caused by the variation in the outer radius of the liquid bridge (r1) and the neck radius of the liquid bridge (r2). With an increase in volumetric water content and sphere diameter, the increasing rate of r1 is much higher than r2, and the macroscopical matric suction gradually decreases.